2020
DOI: 10.3389/feduc.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Idea Emergence in Subject-Matter Collaborative Learning

Abstract: Idea emergence is critical in learning as knowledge creation. Although recent advancements make it possible to detect emergent ideas and evaluate how students engage in knowledge creation in collaborative learning contexts, the relationship between the learning processes and final conceptual understanding has not been well-studied. One confounding factor is how much students engage in their study topic during collaboration. In this study, therefore, we propose a new procedure for evaluating idea emergence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Specifically, there was a significant positive relationship between the frequency of SSR and the physics score (r= 0.68, p=0.007). Similar results were also reported by Oshima et al (2020) and our results confirm other findings on the important relations between collaborative metacognitive regulation (Winters & Alexander, 2011) and socially shared regulation (Järvelä et al, 2016) and learning performance. A plausible explanation is that students find it hard to solve the challenge tasks on their own, and this increases their awareness and need for socially shared regulation.…”
Section: Rq1: What Is the Nature Of Cps Regulation Activated By Students When They Work In Groups On Three Different Types Of Physics Modsupporting
confidence: 93%
“…Specifically, there was a significant positive relationship between the frequency of SSR and the physics score (r= 0.68, p=0.007). Similar results were also reported by Oshima et al (2020) and our results confirm other findings on the important relations between collaborative metacognitive regulation (Winters & Alexander, 2011) and socially shared regulation (Järvelä et al, 2016) and learning performance. A plausible explanation is that students find it hard to solve the challenge tasks on their own, and this increases their awareness and need for socially shared regulation.…”
Section: Rq1: What Is the Nature Of Cps Regulation Activated By Students When They Work In Groups On Three Different Types Of Physics Modsupporting
confidence: 93%
“…KBDeX has been used to examine discourses leading to different levels of learning outcomes. Oshima et al [23] examined knowledge-building discourse among groups of high school students learning the human immune system in a science classroom, analyzing the discourse data using KBDeX and calculating the term frequencies of subject-related words used in the discourse. Oshima et al found no significant differences in mean term frequencies of subject-related words across groups; however, the temporal trajectories of the total values of degree centrality of words were different between high and low learning outcome groups, with the trajectory of high learning outcome groups continuously increasing over time.…”
Section: Studies Using Kbdexmentioning
confidence: 99%